Diversity and distribution of fern species in selected trail in Kuantan Pahang - Sahrom, Izyan Nazihah; Zaini, Mohd Shahir; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Muhamad Tajudin, Nur Shuhada (Zibeline International Publishing Sdn. Bhd., 2018)
A study on the diversity and distribution of terrestrial and epiphytic fern in Kuantan, Pahang was conducted from January to November 2017. Fourteen species of both terrestrial and epiphytic ferns, respectively have been collected and examined from five districts of Kuantan namely Kuala Kuantan, Ulu Kuantan, Penor, Ulu Lepar and Sungai Karang. This study was carried out to examine and evaluate the distribution and to assess the abudance of epiphytic fern in Kuantan, Pahang. The materials obtained for this study were collected from sampling sites and prepared as herbarium voucher. Morphological characteristics were studied, observed and annotated. Based on this study, the terrestrial and epiphytic fern families namely Nephrolepidaceae, Gleicheniaceae, Lygodiaceae, Lindsaeceae, Woodiaceae and Thelypteridaceae, Polypodiaceae, Pteridaceae, Davalliaceae, Aspleniaceae, Blechnaceae and Cyatheaceae were recorded. It mostly can be found in the rainforest area. An updated checklist of terrestrial and epiphytic ferns has been prepared for comparison and future reference.